A Prospective Study of the Causes of Bruises in Premobile Infants. Issue 2 (February 2020) - Feldman, Kenneth W.; Tayama, Tricia M.; Strickler, Leslie E.; Johnson, Lee A.; Kolhatkar, Gauri; DeRidder, Catherine A.; Matthews, Dana C.; Sidbury, Robert; Taylor, James A.
Abstract : Objective: This study had 2 objectives. First, to determine the behavior of physicians evaluating premobile infants with bruises. Second, and most importantly, to learn whether infants with unexplained bruising who had been initially evaluated by primary care and emergency department (ED) physicians are as likely to have their bruises attributed to child abuse as those children evaluated by child abuse physicians. Methods: Primary care, ED, and child abuse pediatricians (CAPs) in King County, Washington, San Mateo, Calif, Albuquerque, NM, La Crosse, Wis, and Torrance, Calif prospectively identified and studied infants younger than 6 months with less than 6 bruises, which were judged by the evaluating clinician to be explained or unexplained after their initial clinical examination. Results: Between March 1, 2010, and March 1, 2017, 63 infants with initially explained and 46 infants with initially unexplained bruises were identified. Infants with unexplained bruises had complete coagulation and abuse evaluations less frequently if they were initially identified by primary care pediatricians or ED providers than by CAPs. After imaging, laboratory, and follow-up, 54.2% (26) of the infants with initially unexplained bruises, including 2 who had been initially diagnosed with accidental injuries, were diagnosed as abused. Three (6.2%) infants had accidental bruising, 6 (12.4%) abuse mimics, 1 (2.5%) self-injury, 1 (2.5%) medical injury, and 11 (22.9%) remained of unknown causation. None had causal coagulation disorders. A total of 65.4% of the 26 abused infants had occult injuries detected by their imaging and laboratory evaluations. Six (23.1%) abused infants were not diagnosed until after they sustained subsequent injuries. Three (11.5%) were recognized abused by police investigation alone. Thirty-eight percent of the abused, bruised infants had a single bruise. Clinicians' estimates of abuse likelihood based on their initial clinical evaluation were inaccurate. Primary care, ED, and child abuse physicians identified abused infants at similar rates. Conclusions: More than half of premobile infants with initially unexplained bruises were found to be abused. Abuse was as likely for infants identified by primary care and ED providers as for those identified by CAPs. Currently, physicians often do not obtain full abuse evaluations in premobile infants with unexplained bruising. Their initial clinical judgment about abuse likelihood was inadequate. Bruised infants often have clinically occult abusive injuries or will sustain subsequent serious abuse. Bruised infants should have full abuse evaluations and referral for Protective Services and police assessments.